2013
DOI: 10.1007/s11010-013-1824-2
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorating effect of eugenol on hyperglycemia by attenuating the key enzymes of glucose metabolism in streptozotocin-induced diabetic rats

Abstract: Epidemiological studies have demonstrated that diabetes mellitus is a serious health burden for both governments and healthcare providers. This study was hypothesized to evaluate the antihyperglycemic potential of eugenol by determine the activities of key enzymes of glucose metabolism in streptozotocin (STZ)-induced diabetic rats. Diabetes was induced into male albino Wistar rats by intraperitoneal administration of STZ (40 mg/kg body weight (b.w.)). Eugenol was administered to diabetic rats intragastrically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
48
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(70 citation statements)
references
References 47 publications
12
48
0
4
Order By: Relevance
“…It was reported that phenolic compounds exert antioxidant, antidiabetic, anticancer etc [17][18][19][20]. Eugenol and isoeugenol, phenolic compounds identified from Balanites aegyptiaca (L) Del 's extracts in our study have been reported to exert antidiabetic activity among other pharmacological roles [19,20]. Based on this, one may suggests that the phenolic compounds identified from Balanites aegyptiaca (L) Del account for its vast medicinal properties particularly antidiabetic activity.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…It was reported that phenolic compounds exert antioxidant, antidiabetic, anticancer etc [17][18][19][20]. Eugenol and isoeugenol, phenolic compounds identified from Balanites aegyptiaca (L) Del 's extracts in our study have been reported to exert antidiabetic activity among other pharmacological roles [19,20]. Based on this, one may suggests that the phenolic compounds identified from Balanites aegyptiaca (L) Del account for its vast medicinal properties particularly antidiabetic activity.…”
Section: Resultssupporting
confidence: 64%
“…Among the identified compounds, phenolics have been reported to account for various pharmacological or biological activities. It was reported that phenolic compounds exert antioxidant, antidiabetic, anticancer etc [17][18][19][20]. Eugenol and isoeugenol, phenolic compounds identified from Balanites aegyptiaca (L) Del 's extracts in our study have been reported to exert antidiabetic activity among other pharmacological roles [19,20].…”
Section: Resultssupporting
confidence: 50%
“…Previous studies have found that clove extracts and eugenol, the major bioactive component of clove, significantly reduce blood glucose level in animal models, and inhibit PEPCK and G6Pase gene expression in hepatocytes. 12,13,34,35 The present study explored the potential mechanisms of SE on metabolism in comparison to metformin, insulin, and resveratrol. It has been reported that metformin increases insulin sensitivity, enhances peripheral glucose uptake, and increases fatty acid oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Glycogen pathology in human diabetic myocardium was first reported over 80 years ago (96). This is a replicated finding in many diabetic experimental settings (2, 46, 84) and occurs in parallel to a depletion of glycogen stores in the liver and skeletal muscle (30,85,87). The fundamental bases for differential glycogen handling responses in distinct muscle types are still not yet understood.…”
Section: )mentioning
confidence: 92%